A Histological Evaluation of the Efficiency of Using Periprosthetic Autologous Fat to Prevent Capsular Contracture Compared to Other Known Methods—An Experimental Study - Mihaela Pertea; Nadia Aladari; Oxana Madalina Grosu; Stefana Luca; Raluca Tatar; Andrei-Nicolae Avadanei; Madalina Palaghia; Ana Maria Trofin; Sorinel Lunca; Nina Filip (Diagnostics, 2024)
Background: Capsular contracture remains a common complication in silicone breast implantation. The etiology, formation mechanisms, predisposing and favoring factors are still subjects of research. This study aims to demonstrate the effectiveness of using autologous fat introduced periprosthetically in preventing capsular contracture compared to other known methods: antibiotics and corticosteroids. Methods: A cohort of 80 Wistar rats was included in the study, divided into four subgroups. All subjects received a silicone implant, implanted in a pocket created along the abdominal midline. The first subgroup served as the control group, with subjects having the implant placed without any treatment. For the second and third subgroups, the implants were treated with an antibiotic solution and intramuscular injections of dexamethasone, respectively. The subjects in the last subgroup received centrifuged autologous fat introduced periprosthetically. Results: The subgroup with autologous fat exhibited a significantly smaller capsule thickness, which was poorly represented, with a smooth surface. The use of autologous fat for treating silicone prosthesis was linked with the lack of acute inflammation around the prosthetic site. Conclusions: Autologous fat helps to minimize the “non-self” reaction, which results in the development of a periprosthetic capsule consisting of mature collagen fibers interspersed with adipocytes.